Als ik, van uw effen voorhoofd... - Perk, Jacques; Gras, Karel (Antwerpen : Gustave Faes.)
Bibliotheek Camille Huysmans
Partituur voor zang en piano
Nederlands
Partituur
Keywords: partituren; liederen